EFFECT OF BIOFERTILIZER PRODUCED FROM LOCALISOLATES OF PSEUDOMONAS PUTIDA AND PSEUDOMONAS FLUORESCENS BACTERIA ON SOME SOIL CHARACTERISTICS AND YIELD OF WHEAT (TRITICUM AESTIVUM L( A- YIELD COMPONENTS - & et al., Abed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Field experiment was conducted using randomized complete block design with three replicates to evaluate the effect of biofertilizer of Pseudomonas putida and Pseudomonas fluorescens seperatally or together with peatmoss or bentonite as carriers in interaction with four mineral fertilizer levels zero, 25%, 50%, and 75% of the recommended level on the growth and yield of wheat (Alrasheed varity). Tow control treatments were used, the first included no addition of biofertilizer and mineral fertilizer and the second included the addition of the recommended level (100%) of mineral fertilizer. The highest value of grain yield was achieved with the treatment of mixed bacterial isolates with an increment mineral fertilizer which to 5.75 Mgha-1 which increased 41.7% compared to first control treatment and 0.9% over the second control treatment. The highest biological yield was achieved mixed bacterial culture with bentonite and 75% of the recommended level of mineral fertilizer giving 16.20 Mgha-1 with an increment of 18.8% compared to first control treatment and 11.2% over the second control treatment. The weight of 1000 grain was 47.43g which increased by 21% over the first control treatment and7.4% over the second control treatment with the treatment that include the addition of Pseudomonas fluorescens with bentonite and 50% of the recommended level of mineral fertilizer.